Inclusive Curriculum in Nepal's Context - Rapacha, Lal-Shyãkarelu (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Inclusive curriculum in contemporary Nepal’s technical and higher education policy, programme, content and system is a dire need for making our education innovative technically and more competitive globally since our policy, programme, content and system till date have remained monolithic - thus feudalistic in structure as well as nature and in content mainly dominated by western colonial principle rather than by our own national indigenous knowledge. Nepal within her (its) national boundary, has a rich vein of indigenous knowledge (i.e. tangible and intangible cultural heritage including languages, cultures, archaeology, belief systems, ethnobotany, ethnomedicine etc) and skills (most of them are endangered and extinct now) just waiting to be tapped by the inclusive policy of government and private educational sector in the country. Therefore, the main purpose of this article is to explore new paradigm shift in our education policy, programme, content and system by making our curriculum much more inclusive in the process of knowledge-building and sustainability through an indigenous perspective with some empirical but selective and limited knowledge inventories. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10472 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 85-102